Primary healthcare teams' views on using mortality data to review clinical policies. Issue 5 (3rd October 2007) - Sullivan, Emma; Baker, Richard; Jones, David; Blackledge, Hanna; Rashid, Aly; Farooqi, Azhar; Allen, Justin
Abstract : Background and objective: A UK-wide scheme to monitor mortality in general practices has been recommended to improve safety. A monitoring scheme might also have a role in improving quality by informing clinical policies. This study investigated the views of primary care teams on the desirable characteristics of mortality data to help them review and plan their clinical policies. Setting: 10 general practices in Leicestershire, UK. Methods: Development of a format for presentation of mortality data for primary care teams, presentations of the data to team meetings, and subsequent interviews of 16 general practitioners and nurses to identify issues about the improvement and use of the data for informing clinical policies. Results: The presentation was important in helping teams to understand the data. Comparisons should be between practices with similar patient populations, and information provided on deaths from diseases potentially amenable to prevention through clinical intervention. Practice teams used the data in reflecting on their own clinical care. Conclusions: Presentation of data about mortality in practice populations can enable practices to reflect on their clinical policies. The proposed national scheme for monitoring mortality should provide data in a format that helps teams to improve the quality of care as well as improve patient safety.